1968
DOI: 10.1042/bj1080771
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical studies of a low-molecular-weight form of urease

Abstract: 1. A new form of enzymically active jack-bean [Canavalia ensiformis (L.) DC] urease corresponding to an S(20,w) value of 11.8s and a molecular weight of 260000 was investigated. 2. Conversion of 18s urease (EC 3.5.1.5) into the 12s form depends on both low protein concentration and pH. Above pH5.3 urease exists in the 18s form and below pH4.8 in the 12s form; between these two pH values a 12s-18s rapid-equilibrium process is observed. 3. Comparison of the properties of 18s and 12s urease indicated no major dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

1969
1969
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 18 publications
(11 reference statements)
2
5
0
Order By: Relevance
“…ysteine, lysine and Reithel et al (1964), Sehgal & Naylor (1966 and ,ttem of the digest we in the present work have isolated urease of iumber of resolved specific activity in the range 160-180 Sumner but three of these units/mg. at 22-25°; the purity of the preparations No 'core' material has been demonstrated by ultracentrifugation (Reithel et al 1964), polyacrylamide-gel electroylamide-gel electrophoresis (Blattler et al 1967;Tanis & Naylor, 1968), Estigation are sum-and confirmed by the latter technique and Nlard proteins had terminal studies in the present work. The specific ) their molecular activity of these preparations is but little changed rtionship between from the 129 Sumner units/mg.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…ysteine, lysine and Reithel et al (1964), Sehgal & Naylor (1966 and ,ttem of the digest we in the present work have isolated urease of iumber of resolved specific activity in the range 160-180 Sumner but three of these units/mg. at 22-25°; the purity of the preparations No 'core' material has been demonstrated by ultracentrifugation (Reithel et al 1964), polyacrylamide-gel electroylamide-gel electrophoresis (Blattler et al 1967;Tanis & Naylor, 1968), Estigation are sum-and confirmed by the latter technique and Nlard proteins had terminal studies in the present work. The specific ) their molecular activity of these preparations is but little changed rtionship between from the 129 Sumner units/mg.…”
Section: Discussionsupporting
confidence: 69%
“…The smallest active unit yet found has a molecular weight of about 240 000 (Blattler et al 1967;Tanis & Naylor, 1968), and the data of Kobashi et al (1966) suggest that this unit has only one active site. It might therefore be anticipated that further dissociation would result in inactivation, and this does in fact happen when the structural subunit is produced by dissolving polymeric urease in 6M-guanidine hydrochloride (Tanis & Naylor, 1968) or in sodium dodecyl sulphate (Gorin, Mamiya & Chin, 1967). However, both of these reagents inactivate many enzymes (Reithel, 1963), and in this case it is not possible to separate the effect of denaturation from that of dissociation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pathway enrichment showed that response to copper ion and cellular response to copper ion were enriched in M3. Copper has been proven to play a major role in NAFLD [ 38 ], and copper homeostasis could counteract the progression of NAFLD [ 39 ]. In the hub genes of M3, SNCA and APOE were reported to be associated with copper ion related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…must be entered in mol/kgw. To convert the given units of g/l to mol/kgw, the molecular weight of urease is approximated at 480,000 g/mol (Tanis et al 1968). Additionally, for dilute solutions as this, 1 liter of water is approximately 1 kg of water.…”
Section: 11b Implementationmentioning
confidence: 99%